The Influence of the Intelligence of Transglobal Leadership on Good Governance-Based Forest Management - Muhammad, Fadel; Hendroyono, Bambang; Supriyono, Bambang; Wijaya, Andy Fefta (UI Scholars Hub, 2018)
In recent years the discussion about leadership in public sector has become an interesting topic which has attracted attention from many people with various backgrounds. In public sector, the demand for a great leader has also rapidly increased among society due to the need to provide the effectiveness of policy, resources allocation, time management and mobilizing participation. In Indonesia, forestry is seen as one of vulnerable sectors that need better leadership due to the failure of effective policy implementation such as massive illegal logging, forest fires or other problems causing deforestation. This study aims at analyzing the influence of Intelligence of Transglobal Leadership toward Good Governance-Based Forest Management by applying quantitative approach with survey method conducted in Community Forest (HTR) area over 26 Provinces in Indonesia covering regions from Aceh to Papua. The finding of this inquiry indicates significant influence of intelligence of transglobal leadership toward good governance based forest management by positive value of 0.359 on its coefficient structural model and 2.38 on Critical Ratio. It can be inferred that the intelligence of tranglobal leadership is essential for policy maker within forestry sector in Indonesia.